An ns-3 model for multipath communication with terrestrial and satellite links - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
Some terrestrial Internet access links provide only low data rates. Internet access via geostationary satellites on the other hand provides data rates of up to 50 Mbit/s, but suffers from high latencies. The combination of low data rate, low latency Internet access (e.g., DSL light) and high data rate, high latency Internet access (e.g., geostationary satellites) can utilize the advantages of both. We discuss multipath communication architectures and scheduling strategies for such heterogeneous link combinations. The solution described in this paper relies on Split TCP and Performance Enhancement Proxies. We implement and evaluate the solution with the network simulator ns-3. A well-established traffic model for loading websites is enhanced with different HTTP variants. The results show that the combination of heterogeneous link types can result in page load times close to as if there was a high data rate, low latency Internet access.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Hybrid access; Multipath communication; Network simulation; Terrestrial and satellite networks